2022
DOI: 10.3390/agriculture12101563
|View full text |Cite
|
Sign up to set email alerts
|

Technology of Microclimate Regulation in Organic and Energy-Sustainable Livestock Production

Abstract: The control of climatic conditions where cattle are kept is one of the challenges in the livestock sector regarding the digital automation of the process. (1) Background: The main purpose of this study is to define the optimal foundations for automatic climatic systems in organic and energy-sustainable livestock production. In particular, the following components are suggested: (a) the determination of current deviations and interdependency between factors; (b) an algorithm for defining the possible sources of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…This is fully supported by the conclusions of van Hilten et al ( 2020) that state that transparency of the food supply system can be ensured by blockchain technology, but for many reasons, including economic feasibility, it does not have to be accompanied by the inclusion of the food supply chain in a fully decentralized system. • This research supports the study by Havelka et al (2022) that states that all microclimatic factors in agricultural production sites can now be coordinated electronically with certification bodies. This will lead to more precise regulation of microclimate in the areas of agricultural production.…”
Section: Figuresupporting
confidence: 84%
“…This is fully supported by the conclusions of van Hilten et al ( 2020) that state that transparency of the food supply system can be ensured by blockchain technology, but for many reasons, including economic feasibility, it does not have to be accompanied by the inclusion of the food supply chain in a fully decentralized system. • This research supports the study by Havelka et al (2022) that states that all microclimatic factors in agricultural production sites can now be coordinated electronically with certification bodies. This will lead to more precise regulation of microclimate in the areas of agricultural production.…”
Section: Figuresupporting
confidence: 84%
“…Despite its importance, a relatively limited number of literature is dedicated to barn lighting studies. In a recent work by Havelka et al (2022), they delineated the optimal lighting range to address cows' basic needs as falling between 100 and 160 lx (where 1 lx represents the lumen flux impacting a 1 m 2 area) In contrast, the ASAE (2005) posits that to positively influence cows' milk yield, lighting should be maintained at 150 lx for a period of 16-18 h daily. However, when analyzing building structures and the possibility of using solar radiation (Marciniak, 2008;Angrecka et al, 2017), it is necessary to determine lighting conditions for different barn sections given their non-uniform nature.…”
Section: Management Of Light Environment For Dairy Cattle Welfare Lig...mentioning
confidence: 99%
“…Wood ash is used to speed up the release of gelatin as a slow-release fertiliser.using wood ash, a low-cost plant biomass waste product. Wood ash decreases the capacity of water intake while increasing the uploading capacities of urea.In [36],author's have concluded that,microclimate control: One of the issues in the livestock industry is the regulation of the climate in which cattle are maintained. The digital automation procedures may be used to create a climate that is dependent on the surroundings.…”
Section: Futurementioning
confidence: 99%